KONTRIBUSI PETANI MINYAK KAYU PUTIH TERHADAP SOSIAL EKONOMI MASYARAKAT DI DESA WAEHATA KECAMATAN WAELATA KABUPATEN BURU - Nurlatu, Dewan; Tumengkol, Selvie M.; Mumu, Rudy (HOLISTIK, Journal Of Social and Culture, 2019)
Development is primarily a business activity that is done to make a situation better in the future. Some of the factors that affect agricultural development in the context of national development is an issue that indirectly affect development in the village of Waehata lies in the problem of farmers ' skills and education are limited. Agriculture as one of the economic activities of the community i.e. farmer eucalyptus oil need to get attention because as noted that agriculture is the Foundation of the development of the economic activities of the community. Waehata village community is largely a farmer eucalyptus oil as the main livelihood.Eucalyptus plants contribute to the socio-economic community in the village of Waehata sub-district of Waelata Regency Buru i.e. can increase people's income in addition also eucalyptus plants can be planted in crops such as intercropping bananas, cassava, peanuts and others. With the presence of eucalyptus plant that is free in nature and effort throughout the Community (Customs) can buy livestock or other items as savings and also absorb the workforce so as to strengthen the ties that bind.The success of a village is the human resources (HR) turns out in the village of Waehata level of public education is still low so that necessary cooperation efforts between the Government and local communities to improve education. Incomes vary due to several factors, among others: culture, nature, Weather, health, education costs (capital).Keywords: eucalyptus, socio-economic, farmer